Valoração econômica no monumento natural das falésias de Beberibe-CE: análise sob a perspectiva da sustentabilidade e turismo - Freitas, Mônica Carvalho (2024)
Units of conservation (UCs) are protected natural spaces with the objective of preserving and maintaining the environmental services generated by ecosystems for all society. They are considered one of the viable mechanisms of environmental public policies for the preservation of environmental quality and human well-being. Therefore, the involvement of society in the management of these spaces offers a new vision of value to natural resources, including the perception of them as financial assets of great relevance in the local and global economy. Through environmental economic valuation, it is possible to outline exclusive public policies for each context and use of natural resources, in addition to subsidizing the accounting of environmental impacts arising from the interaction between man and nature. In this context, the present research has as its main objective to estimate the environmental economic value of the Beberibe Cliffs Natural Monument-CE, through the willingness to pay (WTP) of people, for the conservation and preservation of environmental quality and the natural riches found in the UC. The estimation of WTP and the result of this research can serve as a basis for the establishment of guidelines and effective actions aimed at the sustainable use of the Natural Monument without underestimating the local economic development.